Importance of human capital development and competitiveness in enhancing competency level among Malaysia university graduates : literature review - Marfunizah Ma’dan; Muhamad Takiyuddin Ismail; Sity Daud (Penerbit Universiti Kebangsaan Malaysia, 2019)
The investments in higher education and human capital development in enhancing the competency level among university graduates is one of the main issues in Malaysia. Through this human capital development, the country can generate more competitive graduates with the aims to meet current challenges in a competitive job market. However, based on a secondary review, this research found that the level of competency among graduates assessed through their knowledge, skills and attitudes to manage their field of work not only requires the aspects of human capital such as technical skills, interpersonal skills and conceptual skills, but also the development of competitive attitudes among graduates also need to be emphasized. Therefore, this article review outlines the dimension of emerging human capital and competitiveness aspects with the purpose to improve the competency level among university graduates. In addition, this research proposes a conceptual framework to increase the level of competency among university graduates. Finally, the researchers also give some suggestions to reduce unemployment rates among current university graduates.